2010
DOI: 10.1371/journal.pone.0014200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Thrombospondin-1 Deficits in Astrocyte-Mediated Spine and Synaptic Pathology in Down's Syndrome

Abstract: BackgroundDown's syndrome (DS) is the most common genetic cause of mental retardation. Reduced number and aberrant architecture of dendritic spines are common features of DS neuropathology. However, the mechanisms involved in DS spine alterations are not known. In addition to a relevant role in synapse formation and maintenance, astrocytes can regulate spine dynamics by releasing soluble factors or by physical contact with neurons. We have previously shown impaired mitochondrial function in DS astrocytes leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 114 publications
5
92
0
Order By: Relevance
“…Furthermore, TSP1 levels were markedly reduced in astrocytes from patients with Down’s syndrome. The restoration of TSP1 levels rescued the spine and synaptic defects found in hippocampal neurons cultured in the presence of Down’s syndrome astrocytes 107 . These results indicate that astrocyte-secreted molecules contribute to the synaptic defects in Down’s syndrome and raise the question of whether TSP1 could be used to treat these synaptic defects.…”
Section: Implications For Human Health and Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, TSP1 levels were markedly reduced in astrocytes from patients with Down’s syndrome. The restoration of TSP1 levels rescued the spine and synaptic defects found in hippocampal neurons cultured in the presence of Down’s syndrome astrocytes 107 . These results indicate that astrocyte-secreted molecules contribute to the synaptic defects in Down’s syndrome and raise the question of whether TSP1 could be used to treat these synaptic defects.…”
Section: Implications For Human Health and Diseasementioning
confidence: 91%
“…The cognitive deficits in patients with Down’s syndrome have been associated with structural changes in the architecture and alterations in the number of dendritic spines 106 . Hippocampal neurons grown in the presence of astrocytes from patients with Down’s syndrome have abnormal spine development and reduced synaptic density and activity 107 . This study identified TSP1 as the key astrocyte-secreted factor that modulates spine number and density.…”
Section: Implications For Human Health and Diseasementioning
confidence: 99%
“…Astrocytes secrete a number of molecules that are not defined as gliotransmitters but that nevertheless directly modulate synaptic structures and thereby synaptic function (23) on a slower time scale. We focused on one class of these, the TSPs, because (a) they bind to synaptic α 2 δ-1 receptors to induce excitatory synaptogenesis in vitro and in vivo; (b) gabapentin, which inhibits this synaptogenic action by antagonizing TSP binding to α 2 δ-1, is effective against neuropathic pain (32); (c) dendritic spine malformations and reduced synaptic density in Down syndrome brain are directly linked to deficits in astrocytic TSP-1 protein expressions (56); and (d) astrocytes near the injured neuronal cell bodies release TSPs to cause functional and structural synaptic plasticity in vitro and in vivo (50,55). We found that TSP-1 release from S1 astrocytes is markedly increased 1 9 9 3 jci.org…”
Section: Methodsmentioning
confidence: 99%
“…In Down's syndrome, a related neurodevelopmental disorder caused by trisomy of chromosome 21, astrocytes also do not support neuronal development or synapse formation, with WT neurons showing immature spines when cultured with Down's syndrome astrocytes. Interestingly, Down's syndrome astrocytes show decreased expression of multiple synaptogenic proteins including TSP1 and Gpc6, and like with Fragile X syndrome, the addition of TSP1 to Down's syndrome astrocytes is sufficient to rescue some of the synaptogenic deficits (Chen et al, 2014; Garcia et al, 2010). Finally in Costello syndrome, caused by mutations in HRAS, an opposite alteration in astrocyte function is observed.…”
Section: Astrocyte-synapse Interactions Are Disrupted In Neurodevelopmentioning
confidence: 99%